2022
DOI: 10.1128/spectrum.01106-22
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs Represent a Novel Class of Human Cytomegalovirus Transcripts

Abstract: HCMV infects 40% to 100% of the human population globally and may be a life-threatening pathogen in immunocompromised individuals. CircRNA is a family of unique RNA that is the most newly found and remains unknown in many aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…CircRNAs are an alternative splicing product and thus expand the number of transcripts without extending genome size; a strategy that may be advantageous for organisms with limited coding space. In line with this hypothesis, recent studies have experimentally confirmed viral circRNAs expressed by beta-and gamma-herpesviruses, human papillomavirus, Merkel cell polyomavirus, hepatitis B virus, respiratory syncytial virus, and coronaviruses; with bioinformatic evidence for many other viruses (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…CircRNAs are an alternative splicing product and thus expand the number of transcripts without extending genome size; a strategy that may be advantageous for organisms with limited coding space. In line with this hypothesis, recent studies have experimentally confirmed viral circRNAs expressed by beta-and gamma-herpesviruses, human papillomavirus, Merkel cell polyomavirus, hepatitis B virus, respiratory syncytial virus, and coronaviruses; with bioinformatic evidence for many other viruses (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 78%
“…Since circRNAs lack 5' and 3' ends they have low immunogenicity and extended halflives that average ~2.5 times longer than their linear counterparts (14,26). CircRNAs generally function to regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…A newly published work by Yang et al. biomatically predicts HCMV-encoded circRNAs based on transcriptomic data from NCBI GEO database and validate viral circRNA expressions in cells infected by different clinical HCMV strains (TB40/E, Towne and Toledo, respectively) ( Yang et al., 2022 ). Their results suggest that the expression patterns of HCMV circRNAs are different between different strains and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that circRNA plays important biological functions including microRNA (miRNA) sponges, parental gene expression regulators, and the translation template ( 2 5 ). Viral circRNAs have been recently identified from cells infected with different DNA viruses, such as Epstein-Barr virus (EBV) ( 6 , 7 ), Kaposi’s sarcoma-associated herpesvirus (KSHV) ( 8 ), human papillomaviruses (HPVs) ( 9 ), and human cytomegalovirus (HCMV) ( 10 ). Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a worldwide pandemic and poses a high threat to global health.…”
Section: Lettermentioning
confidence: 99%